2016
DOI: 10.1097/wnq.0000000000000152
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intracranial Extradural Meningiomas

Abstract: Objective: We reviewed 17 cases of primary intracranial extradural meningiomas (PIEMs) (including our 5 cases) reported in the literature so as to develop a better understanding of their clinical characteristics, treatment, and prognosis. Materials and Methods:The clinical data of 17 cases of PIEMs, including our 5 cases, were analyzed on their demographic features, presenting symptoms and duration, imaging and surgical findings, surgical results, pathologic grades, histologic subtypes, and follow-up results.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Combined with a previous review of 178 reported cases from the English language medical literature by Lang et al [8], Gibson cited an additional 100 cases of PEM at the time of publication of their chapter (2009). In this author's brief survey of the entire medical literature not restricted to the English language from 1/1/2008 to the present, approximately 184 cases of PEM are noted after using search terms that Gibson identified as descriptors for PEMs such as "ectopic", "extracranial", "extraneuraxial", "extradural", "cutaneous", "calvarial", "intraosseous" and "meningioma".…”
Section: Primary Ectopic (Extracranial) Meningiomasmentioning
confidence: 97%
“…Combined with a previous review of 178 reported cases from the English language medical literature by Lang et al [8], Gibson cited an additional 100 cases of PEM at the time of publication of their chapter (2009). In this author's brief survey of the entire medical literature not restricted to the English language from 1/1/2008 to the present, approximately 184 cases of PEM are noted after using search terms that Gibson identified as descriptors for PEMs such as "ectopic", "extracranial", "extraneuraxial", "extradural", "cutaneous", "calvarial", "intraosseous" and "meningioma".…”
Section: Primary Ectopic (Extracranial) Meningiomasmentioning
confidence: 97%